Groundwater Regime under Blue-gum at Osamund Nilgiris-initial Observations - Mathur, H. N.; Franois Hilary Raj, S. (Indian Forester, 1980)
Groundwater table fluctuations occurring under Eucalyptus globulus plantation has been measured to study the possibility of depletion of groundwater by Eucalyptus plantations. A series of piezometric holes were driven along a hill up with Eucalyptus globulus (Blue-gum) and a part covered with grassland and Shola at Osamund, Wenlockdowns reserved forest in the Nilgiris. The sub-soil water levels were monitored once daily. The depth of groundwater (December, 1979) varied between 15m in well in the low-laying area to 4.5m in well at the top of the slope whereas the corresponding figures (March, 1980) were 2.19m for well in low-lying areas and 6.2m for well at the top of the slope These groundwater table levels are much below the general rooting zone 2m of Eucalyptus except in the well in low-lying areas. This indicates that Eucalyptus gobulus does not tap groundwater table during December to March.